Food insecurity and social support as determinants of health outcomes among patients attending rural HIV clinic in Bushbuckridge, South Africa - Lweno, Omar (My University, 2010)
Abstract not included on cd
MSc (Med) Epidemiology and Biostatistics, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: food insecurity; malnutrition; social support; HIV; rural clinic